Neurophysiological correlate of emotional regulation in cognitive and motor deficits in Tourette's syndrome. (14th September 2019) - Kalsi, Navkiran; Tambelli, Renata; Altavilla, Daniela; Trentini, Cristina; Panunzi, Sara; Stanca, Mariella; Aceto, Paola; Cardona, Francesco; Lai, Carlo
Abstract: Objectives: The present study investigated the role of different emotions in the expression of cognitive and motor control abilities of children having Tourette's syndrome (TS) compared to healthy controls. Methods: The electroencephalography activity of 33 children (mean age in final sample: TS ( n  = 10) = 10.5 ± 2.3; control ( n  = 10) = 10.1 ± 2.9) was recorded during a visual task consisting of four emotional face cues (anger, happiness, neutral and sadness) followed by a target in congruent or incongruent position with emotional cue. The participants were asked to indicate the target location. Results: The TS patients showed a shorter latency of the P1 and N170 only for anger cues compared to controls. In addition, sLORETA results showed an increased activation in the left occipital area and a decreased activation in the left amygdala, temporal and cingulate for anger cues in TS patients. Coherently, TS patients showed a lower accuracy of response only with anger cue and severity of tics resulted correlated with the event-related potentials data and behavioural responses linked to anger cue. Conclusions: These results suggest that children with TS process emotions (in particular the anger) differently from the controls, and that its regulation seems to have an important role in the cognitive and motor deficits in TS.